Country Partnership Framework for the Repbulic of El Salvador for the Period FY2016-FY2019 - World Bank Group (World Bank, Washington, DC, 2015)
El Salvador is the smallest country in Central America, and one of the most densely populated in the world. El Salvador is among the countries most affected by weather-related events and other hazards, incurring annual losses of around 2.5 percent of GDP. Worldwide, it ranks second highest for risk exposure to two or more hazards and highest for the total population at a relatively high risk of mortality. Furthermore, climate change is expected to increase the frequency and severity of weather, related events. The new Administration is committed to making El Salvador more ‘productive, educated, and safe’ by promoting inclusive growth and resilience. The World Bank Group’s (WBG) proposed new CPF intends to promote inclusive growth and to foster resilience, with a focus on policy levers that could contribute to break the vicious circles in a sustainable manner. The proposed CPF is aligned with the Government’s priorities and informed by the WBG’s recent SCD. To strengthen the mutually-reinforcing foundations of inclusive growth, the proposed WBG engagement would support objectives which seek to: (i) build capacity to create safer communities for economic development; (ii) improve secondary-school attainment; (iii) enhance youth employability and skills; and (iv) increase access to finance. To foster sustainability and resilience, the proposed CPF seeks to: (v) promote the efficiency of public spending; and (vi) build capacity to manage disasters and environmental challenges. Taking into account the challenges faced by El Salvador, the WBG wishes to provide a modest but catalytic role through the implementation of these six objectives.